Impact of social investment in the health system of Bogotá (2013)
This paper briefly discusses the health situation in the Capital District, as a structural element of the investment policy of the Colombian State must develop to meet the needs of its population, for it takes into account the health system, giving primary relevance to the subsidized regime, as this is the main point of reference for the government because it is the population with higher primary needs. The characteristics of the system, its actors are set, the institutions involved, the projects that are being developed, its scope and impact, its limitations and finally some improvement alternatives faced by the difficulties encountered.